2021
DOI: 10.1055/s-0041-1732295
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Leptin and Risk of Future Incident Venous Thromboembolism

Abstract: Background Circulating levels of leptin, an adipocyte-derived hormone, are frequently elevated in obesity. Leptin has been reported to upregulate prothrombotic hemostatic factors in vitro and could potentially mediate venous thromboembolism (VTE) risk in obesity. However, whether leptin is associated with VTE remains uncertain. Objective This article investigates the association between plasma leptin and risk of incident VTE, and the potential of leptin to mediate VTE risk in obesity. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
2
8
1
Order By: Relevance
“…to upregulate the expression of tissue factor and PAI-1 in vitro, 45,46 our results suggest that leptin is not relevant for mediating the VTE risk among obese individuals. 44 The present study supports the hypothesis that PAI-1 is in the causal path between obesity and VTE. PAI-1 mediated almost 15% of the VTE risk in obesity, which was largely independent of chronic low-grade inflammation, as reflected by CRP levels.…”
Section: Ta B L Esupporting
confidence: 89%
See 2 more Smart Citations
“…to upregulate the expression of tissue factor and PAI-1 in vitro, 45,46 our results suggest that leptin is not relevant for mediating the VTE risk among obese individuals. 44 The present study supports the hypothesis that PAI-1 is in the causal path between obesity and VTE. PAI-1 mediated almost 15% of the VTE risk in obesity, which was largely independent of chronic low-grade inflammation, as reflected by CRP levels.…”
Section: Ta B L Esupporting
confidence: 89%
“…For instance, in the Tromsø and REGARDS cohorts, CRP, a marker of inflammation, mediated approximately 15% to 20% of the VTE risk in obesity 30,31 . In a previous nested case‐control study, we investigated the association between leptin, an adipocyte‐derived hormone that is commonly elevated in obesity, and risk of future VTE 44 . Although leptin has been reported to upregulate the expression of tissue factor and PAI‐1 in vitro , 45,46 our results suggest that leptin is not relevant for mediating the VTE risk among obese individuals 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies in non‐RA populations observed that leptin levels and low muscle mass predict mortality in men without prevalent CAD or HF (45). The tendency for leptin to predict VTE events in our study conflicts somewhat with a prior study, which suggested that the association between leptin and VTE is explained by BMI (46). Overall, our findings support the hypothesis that body composition and circulating leptin may be important predictors of CVD risk independent of BMI at least for VTE and CVD‐related death, particularly among thinner patients.…”
Section: Discussioncontrasting
confidence: 99%
“…A prospective study of 203 OA patients reveals that a high preoperative leptin level may be an independent risk factor for postoperative DVT (OR = 2.17, 95% CI, 1.01–4.64) ( Lu et al, 2018 ). However, a recent nested case–control analysis (416 VTE cases and 848 controls) based on the trauma cohort revealed that blood leptin levels were related to the incidence of VTE, before adjusting for BMI, which indicates that the association between circulating leptin levels and VTE risk might be confounded by BMI ( Frischmuth et al, 2022 ). This is consistent with the results of the current MR study.…”
Section: Discussionmentioning
confidence: 99%